jurisprudential theorizing - Sources of jurisprudential theorizing. - Rafed hasan majeed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Many questions come to mind when we know and study the subject of theory and Sharia jurisprudence theory, including what is the position of Islamic law on this theory? Which provisions of the Sharia can be considered and which cannot?The call for a doctrinal analysis of the provisions of the Islamic Sharia is a call consistent with the goals and objectives of the Sharia calling for the rejection of embarrassment, as it is an orientation's for the future of Islamic law.This study allah have come in response to renewal in the contemporary jurisprudential movement, and to life style and the area we live in.